Unveiling Shopee's E-Commerce Success: How eWOM, Promotions, Product Variety, and Security Shape Gen Z and Millennials' Purchase Decisions - Jimmy, Jimmy; Hamzah, Muhammad Luthfi; Rizki, Muhammad (International Journal of Information System and Innovation Management (IJISIM), 2024)
This study aims to analyze the effect of Electronic Word of Mouth (eWOM), Promotion Strategy, Product Diversity, and Transaction Security on Purchasing Decisions. The population of this study consists of Generation Z and Millennials residing in Pekanbaru who have used or currently use the Shopee application. A sample of 100 respondents was selected using the accidental sampling method. The data analysis technique employed is Multiple Linear Regression Analysis, conducted using the SPSS V21 software. The results of the study indicate that Electronic Word of Mouth (eWOM), Promotion Strategy, and Product Diversity variables have a significant positive effect on Purchasing Decisions. In contrast, the Transaction Security variable has a positive but insignificant effect on Purchasing Decisions.